miR-7/SP1/TP53BP1 axis may play a pivotal role in NSCLC radiosensitivity - Guo, Genyan (Oncol Rep, 2020)
MicroRNA-7 (miR-7) has been identified as a tumor suppressor in non-small cell lung cancer (NSCLC) and a radiosensitivity regulator. Numerous studies have revealed that specific protein 1 (SP1) plays a critical role in the tumorigenesis of various types of cancers and regulates radiosensitivity and tumor suppressor p53-binding protein 1 (TP53BP1), which plays an essential role in DNA repair. However, it is not clear whether miR-7 has a regulatory effect on SP1 and TP53BP1 in NSCLC. In the present study it was revealed that miR-7 directly binds to the 3′UTR of SP1, thereby suppressing SP1 expression to regulate radiosensitivity. Overexpression of miR-7 and SP1 and knockdown of miR-7 and SP1 were performed using lentiviral transfection. Protein and mRNA abundance of SP1 and TP53BP1 were determined using western blotting and RT-qPCR, respectively, while miR-7 binding to SP1 was validated using a luciferase reporter assay. Biological function analysis indicated that miR-7 negatively regulated SP1 and inhibited cell proliferation, migration, and invasion when combined with radiation. It was also revealed that the expression of TP53BP1 was positively regulated by SP1 or negatively regulated by miR-7. In conclusion, SP1 was a target of miR-7, and the decreased expression of SP1 resulting from miR-7 overexpression in NSCLC was vital for improving radiosensitivity in NSCLC cells. Moreover, SP1 expression was detected in 95 paired NSCLC and adjacent normal tissues, and it was determined that SP1 was significantly upregulated in NSCLC tissues and that its upregulation was correlated with the degree of tissue differentiation. Thus, SP1 and/or miR-7 may be potential molecular targets in NSCLC radiotherapy.